Remote control using telephone / Azlinawati Mohd. Husain and Norhafiza Mohd Zaid - Mohd. Husain, Azlinawati; Mohd Zaid, Norhafiza (2003)
Here is a teleremote circuit which enables switching ‘on’ and ‘off of appliances through telephone lines. It can be used to switch appliances from any distance, overcoming the limited range of infrared and radio remote controls. The circuit described here can be used to switch up to nine appliances (corresponding to the digits 1 through 9 of the telephone key-pad). For our project we are advised by our supervisor to make the circuit to switch to 3 appliances. The DTMF signals on telephone instrument are used as control signals. The digit ‘0’ in DTMF mode is used to toggle between the appliance mode and normal telephone operation mode. Thus the telephone can be used to switch on or switch off the appliances also while being used for normal conversation.